Repair of thermally damaged concrete cylinders with basalt fiber-reinforced polymer jackets. (December 2021) - Ouyang, Li-Jun; Chai, Mao-Xiang; Song, Jiang; Hu, Li-Li; Gao, Wan-Yang
Abstract: Basalt fiber-reinforced polymer (FRP) material is a new type of FRP composites and has promising potential to repair deficient concrete structures. This paper presents the results of an experimental study on the compressive behavior of thermally damaged circular concrete cylinders repaired with BFRP jackets. The specimens were divided into three series: three reference cylinders tested at ambient temperature, 12 thermally damaged concrete cylinders tested without strengthening, and 36 thermally damaged concrete cylinders tested after repaired with different layers of BFRP jackets. The thermally damaged concrete cylinders were initially exposed to various elevated temperatures ranging from 200 °C to 800 °C with a heating duration of 2.5 h and then cooled down to the ambient temperature. The experimental results, including the failure modes, axial stress-strain curves, compressive strengths, ultimate axial strains, and the hoop strain-to-axial strain relationships of the thermally damaged concrete, were investigated to evaluate the efficiency of BFRP jackets for repairing purpose. Based on the analysis of the test data, it was possible to conclude that the compressive strength enhancements and the ultimate axial strains of the thermally damaged concrete wrapped with BFRP jackets were enhanced with the exposure temperature of the concrete core and the layers of BFRP jackets. Two typical concrete confinement models were then modified by considering the residual mechanical properties of concrete to predict the compressive behavior of the thermally damaged concrete wrapped with BFRP jackets. The comparisons between the model predictions and the test results are presented, and the accuracy of the concrete confinement models are examined and discussed. Highlights: Compressive behavior of thermally damaged concrete cylinders wrapped with BFRP jackets was investigated. Effects of exposure temperature and BFRP jacket layers on the test results were studied. The confinement mechanism of thermally damaged concrete wrapped with BFRP jackets was discussed. The accuracy of typical confinement models for FRP-wrapped thermally damaged concrete was examined.